Dual modification of oil palm leaves-derived silica for simultaneous magnetic solid phase extraction of organophosphorus and organochlorine pesticides in environmental water - Ramli, Fariesha Farha; Wan Ibrahim, Wan Nazihah; Abdul Wahab, Roswanira; Kamaruzaman, Sazlinda; Yahaya, Noorfatimah; Mohamed, Ahmad Husaini; Hanapi, Nor Suhaila Mohamad (Elsevier, 2025)
This study developed a novel sorbent, magnetic silica-3-mercaptopropyltrimethoxysilane (MagSil-MPTMS) with enhanced organophosphorus (OPPs) and organochlorine (OCPs) pesticide extraction from water samples. Pesticide residues were extracted via magnetic solid-phase extraction (MSPE) and quantified using gas chromatography-mass spectrometry (GC-MS; HP-5MS column, splitless injection, selected ion monitoring (SIM) mode). The sorbent was synthesised from sustainable oil palm leave (OPL)-sourced silica and exhibited a mesoporous, aggregated, and rough structure with a high surface area and strong magnetism. Its functional groups, associated with magnetite, silica, and MPTMS, contributed significantly to its selectivity for OPPs and OCPs. The study employed Plackett-Burman screening followed by Box-Behnken optimisation, which identified sorbent mass, sample volume, and pH as the most significant factors influencing the extraction process (p-value <0.05). At 77 mg sorbent mass, 24 mL sample volume, and 5.8 sample pH, the MagSil-MPTMS recorded exceptional extraction efficiency for diazinon, chlorpyrifos, p'p-DDE, and dieldrin, documenting recovery rates and limits of detection between 86.22 % and 114.86 % and 0.59 ng mL−1–0.65 ng mL−1, respectively. The data also corresponded to the limits of quantification and relative standard deviations of 1.79 ng mL−1–1.98 ng mL−1 and 2.61 %–10.77 %, respectively. Moreover, the MagSil-MPTMS sorbent produced in the present study outperformed non-functionalised materials, a promising alternative for pesticide extraction from water samples. The findings championed sustainable waste management by valorising OPL as a renewable silica source. Furthermore, its 5.5 score of Analytical GREEnness (AGREE) metric contributed to the eco-friendliness of the developed sorbent.